Lower Health-Related Quality of Life in Polytrauma Patients: Long-Term Follow-Up After Over 5 Years. Issue 19 (May 2016) - Zwingmann, Jörn; Hagelschuer, Paul; Langenmair, Elia; Bode, Gerrit; Herget, Georg; Südkamp, Norbert P.; Hammer, Thorsten
Abstract : Abstract: Although trauma-associated mortality has fallen in recent decades, and medical care has continued to improve in many fields, the quality of life after experiencing polytrauma has attracted little attention in the literature. This group of patients suffer from persisting physical disabilities. Moreover, they experience long-term social, emotional, and psychological effects that limit/lower considerably their quality of life. We analyzed retrospective data on 147 polytraumatized patients by administering written questionnaires and conducting face-to-face interviews 6 ± 0.8 years after the trauma in consideration of the following validated scores: Glasgow Outcome Scale, European Quality of Life Score, Short Form-36, Trauma Outcome Profile, and Beck Depressions Inventory II. Our analysis of these results reveals that polytraumatized patients suffer from persistent pain and functional disabilities after >5 years. We also observed changes in their socioeconomic situation, as well as psychological after-effects. The rehabilitation of this particular group of patients should not only address their physical disabilities. The psychological after-effects of trauma must be acknowledged and addressed for an even longer period of time.